Evaluation of water, sanitation and hygiene status of COVID-19 healthcare facilities in Ghana using the WASH FIT approach - Mary Eyram Ashinyo (IWA Publishing, 2021)
Access to improved water, sanitation and hygiene (WASH) is essential for the delivery of high-quality care in healthcare facilities and the prevention of hospital-acquired infections such as the transmission of the SARS-CoV-2. In addition, unimpeded access to WASH facilities in coronavirus disease 2019 (COVID-19) treatment centres (TCs) is central in facilitating compliance with infection prevention and control protocols. However, data for the WASH status of COVID-19 TCs in Ghana are limited. We evaluated the WASH status of seven COVID-19 TCs in Ghana using the WHO/UNICEF water and sanitation for health facility improvement tool (WASH FIT). The water domain had the highest number of indicators meeting standards with an average percentage score of 90.5% (range: 66.7–100%) across the seven TCs, followed by management (66.9%) and hygiene (58.7%). The TCs performed poorly in the sanitation and healthcare waste domain, with an average percentage score of 44.6% (range: 22.2–75%). These findings highlight the challenges being faced by COVID-19 TCs in implementing WASH services. Specific WASH interventions are urgently required to strengthen WASH services in the COVID-19 TCs. This should precede the prioritisation of resources to WASH infrastructure in the treatment facilities coupled with actions that involve all stakeholders. HIGHLIGHTS Water, sanitation and hygiene (WASH) in healthcare facilities is crucial in preventing the transmission of highly infectious diseases.; We used the WHO/UNICEF water and sanitation for health facility improvement tool (WASH FIT) to evaluate the WASH status of COVID-19 treatment centres (TCs).; There were gaps in the performance of the TCs across the four WASH domains.; We call for the prioritisation of resources to WASH infrastructure in the TCs.; This is crucial in building a resilient WASH system in the treatment facilities.;